2020
DOI: 10.3390/life10050052
|View full text |Cite
|
Sign up to set email alerts
|

Factoring Origin of Life Hypotheses into the Search for Life in the Solar System and Beyond

Abstract: Two widely-cited alternative hypotheses propose geological localities and biochemical mechanisms for life’s origins. The first states that chemical energy available in submarine hydrothermal vents supported the formation of organic compounds and initiated primitive metabolic pathways which became incorporated in the earliest cells; the second proposes that protocells self-assembled from exogenous and geothermally-delivered monomers in freshwater hot springs. These alternative hypotheses are relevant to the fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 191 publications
(271 reference statements)
0
23
0
Order By: Relevance
“…According to recent literature [ 7 , 36 ], thiophenes per se should not be named biomarkers, due to their possible abiotic origin, but the presence of thiophenes, as easily detectable molecules, could indicate samples or sites, which should be investigated in more detail for the presence of additional organic molecules like amino acids or fatty acids. It is also suggested that terrestrial origin-of-life conditions could be used as a guideline in the search for life on extraterrestrial planets [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent literature [ 7 , 36 ], thiophenes per se should not be named biomarkers, due to their possible abiotic origin, but the presence of thiophenes, as easily detectable molecules, could indicate samples or sites, which should be investigated in more detail for the presence of additional organic molecules like amino acids or fatty acids. It is also suggested that terrestrial origin-of-life conditions could be used as a guideline in the search for life on extraterrestrial planets [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another scenario describes lipid lamellae on the earth's surface with the potential to trap polymers (e.g., short RNA and peptides) undergoing a selection process accompanied by dry/wet cycles. The assumption of the gradual emergence of Darwinian evolution within multiple networks of lipid vesicles based on polymer interactions is presented as the next step but again, no mechanism is provided [2,23]. Lipid vesicles or lamellae may sustain integrity, but positive feedback from the vesicle structure to an information source capable of determining the synthesis of the same stable lipid vesicles is unspecified.…”
Section: The Beginning Of the Biological Structurementioning
confidence: 99%
“…In searching for the first living cell, at some moment, a proto-cell(s) capable of evolving should emerge. The newly established proto-cell must have a relatively simple structure with heredity and a primordial metabolism [1,2]. However, the process leading to the formation of a proto-cell must consist of a multi-step process that begins with the precursors of nucleic acids, peptides, lipids, and energy followed by polymer interactions and enzymatic metabolic reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This generates a hybrid between a pond and a vent, relying on UV light as an energy source like Oparin and Haldane did at a time before anyone knew how cells conserve energy or grow. The hot spring hypothesis [107][108][109] goes back to the warm little pond, with the settings changed in that the pond is fed by hydrothermal springs (providing thermal energy and wet-dry cycles with first molecules possibly coming from meteorites). There is no chemical role for the vent in the hot spring narrative, it just supplies water and salts, nor is there a connection to the lifestyle of the first cells.…”
mentioning
confidence: 99%